2013
DOI: 10.1007/s11033-013-2913-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioceramic-collagen scaffolds loaded with human adipose-tissue derived stem cells for bone tissue engineering

Abstract: The combination of bioceramics and stem cells has attracted the interest of research community for bone tissue engineering applications. In the present study, a combination of Bio-Oss(®) and type 1 collagen gel as scaffold were loaded with human adipose-tissue derived mesenchymal stem cells (AT-MSCs) after isolation and characterization, and the capacity of them for bone regeneration was investigated in rat critical size defects using digital mammography, multi-slice spiral computed tomography imaging and hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Bio-Oss is a deproteinized bovine bone mineral used to treat bone defects, dental implant therapy and healing for alveolar process defects. We also showed, in two previous studies, that Bio-Oss could significantly increase osteogenic differentiation potential of MSCs in vitro and bone regeneration in vivo (23,46). BioOss has a highly porous structure (75% -80 % of the total volume) that increases surface area of the scaffold (47).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Bio-Oss is a deproteinized bovine bone mineral used to treat bone defects, dental implant therapy and healing for alveolar process defects. We also showed, in two previous studies, that Bio-Oss could significantly increase osteogenic differentiation potential of MSCs in vitro and bone regeneration in vivo (23,46). BioOss has a highly porous structure (75% -80 % of the total volume) that increases surface area of the scaffold (47).…”
Section: Discussionsupporting
confidence: 68%
“…Treatment of calvarial defects with ADMSC transplantation has been demonstrated in the literature (20)(21)(22). Daei-farshbaf et al reported that ADMSC seeded on a bioceramic scaffold promoted calvarial bone healing in hypothyroid rats (23). However, the use of stem cells in tissue engineering for bone regeneration had some problems such as expensive cell culture, complicated cell handling and invasive procedure for cell collection from patients (24).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used biomaterials for bone include calcium phosphate ceramics (in particular hydroxyhapatite (HA) [28][29][30] and β-tricalciumphosphate (β-TCP) [28,[31][32][33]), bioactive glasses (mainly silicate-based 45S5 Bioglass ® [34,35]), natural polymers (such as alginate [36], silk [10,29,37] and collagen [38][39][40][41][42]) and synthetic polymers (particularly poly(ɛ-caprolactone) (PCL) [31,32,[43][44][45], poly-L-lactic acid (PLLA) [33], polyglycolic acid (PGA) [45] and polylactid-co-glycolid acid (PLGA) [46,47]) (table 2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Natural and synthetic biomaterials provide three-dimensional differentiation niches to guide the differentiation of SCs towards specific lineages. Bioceramic-collagen scaffolds loaded with human adipose-tissue derived SCs enhanced bone regeneration and reconstruction and also served as appropriate structures in bone regenerative medicine [87]. Furthermore, the combination of biochemical and biophysical stimulatory signals in a three-dimensional setting could potentially enhance the development of mature osteoblasts [88].…”
Section: Increased Differentiation Potentialsmentioning
confidence: 99%